Changes in the rumen Butyrivibrio group in lactating ewes fed a diet supplemented with sunflower oil with or without marine algae - Castro-Carrera T.; Toral P.G.; Hervás G.; Frutos P.; Belenguer A. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
In ruminants, microbial biohydrogenation (BH) of unsaturated fatty acids (FA) can be modulated by diet supplementation with lipids (e.g., sunflower oil -SO- or marine algae -MA-) to improve the fatty acid profile of the milk. The Butyrivibrio group contains the most active biohydrogenating bacteria isolated from the rumen and, for this reason, it has been extensively considered the main responsible for the BH process. With the aim of examining the effect of lipid addition on the Butyrivibrio population, as well as timedependent variations, thirty-six lactating ewes were divided in 6 lots (3 lots/treatment) and offered a diet supplemented with either 2.5% SO or 2.5% SO plus 0.8% MA. After 0, 26 and 52 days on treatments, individual samples of rumen fluid were collected through a stomach tube, composited for each lot, and analysed using the terminal restriction fragment length polymorphism (T-RFLP) molecular technique. Results showed no significant variations, due to either diet or time, in the Butyrivibrio T-RFLP profiles or in the relative abundances of the major terminal restriction fragments (T-RF) detected. However, some less abundant fragments (i.e., representing less than 4.3% of the total) varied significantly. For example, the frequency of a T-RF compatible with 18:0-producing bacteria increased on day 52 in the diet with only SO (from 0.4 to 4.3%), whereas MA addition precluded this effect. The few changes caused in the Butyrivibrio group by a lipid supplementation that is known to alter rumen BH would indicate a low relevance of these bacteria in the ruminal FA metabolism in dairy sheep. Nevertheless, the effect on some small subpopulations would not allow to rule out their involvement in the process.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)